Proximate Analysis and Exponential Model of Activated Carbon from Durian (Durio zibethinus) Peel from South Lampung: Analisis Proksimat dan Model Exponensial Karbon Aktif dari Kulit Buah Durian (Durio zibethinus) Asal Lampung Selatan - Pangestuti, Martasari Beti; Witoyo, Jatmiko Eko; Kurniawan, Randy Yusuf; Cavendish, Amedeo (Universitas Brawijaya, 2025)
Durian (Durio zibethinus) peel is a major agro-waste with high lignocellulosic content and functional groups, making it a promising precursor for activated carbon. This study synthesized and characterized activated carbon from South Lampung durian peel using potassium hydroxide (KOH) activation at 0 M, 1 M, and 2 M. Proximate analysis (moisture and ash content, volatile matter, fixed carbon) was conducted, and exponential regression models were developed to examine the effect of KOH concentration. Results showed significant effects (p < 0.05) of KOH on all parameters. Moisture decreased from 59.23±2.02% to 7.19±3.27%, ash from 6.29±0.31% to 1.45±0.52%, and volatile matter from 7.81±0.45% to 2.09±0.02%, while fixed carbon increased from 84.88±0.31% to 89.72±0.52%. All parameters followed exponential trends with high R² values, indicating strong model fit. These findings confirmed that KOH activation improves activated carbon quality, and exponential models provide predictive insight. Therefore, durian peel from South Lampung is promising for high-quality activated carbon production.